Advancing Educational Practices: Implementation and Impact of Virtual Reality in Islamic Religious Education - Zainal Asril; Syafrimen Syafril; Engkizar Engkizar; Zainul Arifin (Jurnal Pendidikan Islam, 2023)
This research explores the creation of Virtual Reality (VR)-based learning tools for Islamic religious education in Integrated Islamic elementary schools. Following a Research and Development (R&D) methodology, the study employs a six-stage approach: investigation, strategizing, enhancement, assessment, realization, and evaluation (ISI-ARE). The resulting product, a VR-based educational module for teaching the Hajj, undergoes rigorous validation by two VR and animation experts, along with an Islamic religious education teacher. Subsequently, the VR-based learning material is tested on 140 students across four Integrated Islamic Elementary Schools (SDIT) in Padang. Student responses are meticulously collected through questionnaires and analyzed using SPSS version 26.0 software.The outcomes affirm unanimous validation from the three evaluators, establishing the suitability of this media for instructional purposes. Additionally, the analysis identifies eight key aspects of student feedback related to VR-based learning, including comprehensibility of materials, clarity of instructional content, visually stimulating presentation, enjoyable and engaging experiences, a sense of realism, eagerness for repeated VR media utilization, and user-friendly accessibility. This pioneering use of VR-based learning significantly enhances the concreteness, authenticity, and enjoyment of the learning process, introducing novel dimensions and experiences to students. It emphasizes the need to continue designing and developing various VR-based resources to strengthen the teaching of Islamic principles.